1996
DOI: 10.1177/019791839603000207
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary American Attitudes toward U.S. Immigration

Abstract: "This article aims to contribute to an understanding of contemporary American attitudes toward immigration.... The paper uses data from a CBS News/New York Times poll conducted in June 1993. Respondents were asked whether they would like to see the level of immigration to the United States increased, decreased or kept the same. We test several hypotheses about factors influencing respondents' attitudes, including the importance of previously unexamined predictors. These new hypotheses relate to views about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
182
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(195 citation statements)
references
References 10 publications
11
182
0
2
Order By: Relevance
“…Such findings are confirmed by several other studies (Espenshade and Hempstead, 1996;Fetzer, 2000;Chandler and Tsai, 2001;Barkan, 2003;Pantoja, 2006;Wilkes et al, 2008). Some researchers have attributed this strong relationship to labor market factors, claiming that more educated individuals are less likely to face economic competition from immigrants (Espenshade and Hempstead, 1996). And numerous scholars have further asserted that working-class individuals or those at risk of unemployment will be more likely to oppose immigration, given that they will be competing with low-skilled immigrants in the labor market and wish to preserve their economic self-interest (Kessler, 2001;Scheve and Slaughter, 2001;Mayda, 2006;O'Rourke and Sinnott, 2006).…”
Section: Factors and Conditions Influencing Local Immigration Politicssupporting
confidence: 89%
See 2 more Smart Citations
“…Such findings are confirmed by several other studies (Espenshade and Hempstead, 1996;Fetzer, 2000;Chandler and Tsai, 2001;Barkan, 2003;Pantoja, 2006;Wilkes et al, 2008). Some researchers have attributed this strong relationship to labor market factors, claiming that more educated individuals are less likely to face economic competition from immigrants (Espenshade and Hempstead, 1996). And numerous scholars have further asserted that working-class individuals or those at risk of unemployment will be more likely to oppose immigration, given that they will be competing with low-skilled immigrants in the labor market and wish to preserve their economic self-interest (Kessler, 2001;Scheve and Slaughter, 2001;Mayda, 2006;O'Rourke and Sinnott, 2006).…”
Section: Factors and Conditions Influencing Local Immigration Politicssupporting
confidence: 89%
“…For example, in an investigation of the determinants of pro-immigration attitudes in the U.S., Haubert and Fussell (2006) found that holders of advanced university degrees are the most likely to evince positive perceptions of immigrants, whereas individuals without college degrees tend to view immigration unfavorably. Such findings are confirmed by several other studies (Espenshade and Hempstead, 1996;Fetzer, 2000;Chandler and Tsai, 2001;Barkan, 2003;Pantoja, 2006;Wilkes et al, 2008). Some researchers have attributed this strong relationship to labor market factors, claiming that more educated individuals are less likely to face economic competition from immigrants (Espenshade and Hempstead, 1996).…”
Section: Factors and Conditions Influencing Local Immigration Politicssupporting
confidence: 75%
See 1 more Smart Citation
“…The group-threat thesis has been used to study the relationship between the relative size of the foreign-born population in receiving societies and the prevalence of anti-foreigner sentiment among native-born persons in many national and supranational contexts, including Canada, Europe, Israel, Turkey, and the United States (Citrin and Sides 2006; Dixon and Ergin 2010; Espenshade and Hempstead 1996; Quillian 1995, 1996; Rustenbach 2010; Schneider 2008; Semyonov et al 2002, 2006; Pettigrew et al 2010; Wilkes et al 2008). These studies have sought to show whether and under what conditions the size of the foreign-born population acts as a contextual catalyst that elicits anti-foreigner attitudes among native-born individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, immigration in the US has become viewed as one of the most important issues facing the country (Espenshade and Hempstead 1996; Hood III and Morris 1998). Despite a hardening of attitudes toward immigrants and extensive research that describes this public opinion shift, there has been limited empirical research on how public opinion influences immigration policy (Hood III and Morris 1998).…”
Section: Introductionmentioning
confidence: 99%